Incidencia socioeconómica del microcrédito del Bono de Desarrollo Humano en el financiamiento de las actividades agrícolas en las economías campesinas del Cantón Mocache. - Cornejo Dicao, Marjorie Maritza (2013)
Poverty levels experienced by developing countries and particularly those in Latin America, and the resulting social impacts they generate, have led their governments to think and implement social development policies aimed at mitigating and reducing poverty levels and thus contribute to improving the quality of life and reduce the degree of social inequality . In this sense , the present study aims to assess the socioeconomic impact of Microcredit BDH, used in agricultural production activities by the beneficiaries and their families. This work has been developed in a clear and concise, framed in accordance with the legal provisions in the laws of Ecuador, also considering policies and regulations which are summarized in the following chapters. It deals with the conceptual part of the main terms on which research is based microlending, which describes its definition, benefits, micro classes, items, and socioeconomic factors of credit and credit objectives of human development. Analysis will be undertaken on microcredit called "Human Development" for determining and promoting the development of financial markets geared to low-income people, highlighting the profile of the applicant, based on the reality of their economic activity. Finally, in the fourth chapter includes relevant conclusions and recommendations where credit programs related to social development, can be a form of economic initiatives enabled solution for giving a chance to the poor socio-economic development who live in rural areas, also require training and ongoing advice to ensure good use of resources. And therefore it is a real solution.